Occurrence of Citropsis articulata in Tropical Forests in Uganda: Implication for Ex Situ Conservation - Rapheal Wangalwa; Eunice Apio Olet; Grace Kagoro-Rugunda; Casim Umba Tolo; Patrick E. Ogwang; Bernard Barasa (International Journal of Forestry Research, 2021)
Citropsis articulata is a medicinal plant that is increasingly threatened by unsustainable methods of harvesting and habitat degradation. Owing to the fact that this plant species is highly utilized for herbal medicine and is currently restricted to a few forest reserves in Uganda, this has significant implications for ex situ conservation. Therefore, the aim of this study was to assess how physiographical factors influence the occurrence and distribution of C. articulata in the three forest reserves in Uganda, namely, Budongo, Mabira, and Kibale National Park. The study was carried out in 15 compartmental sites in each of the three forests. In each compartmental site, 4 plots of 60 m × 60 m were systematically established, and within each plot, 4 subplots each of size 20 m × 20 m were randomly setup. A total of 240 subplots were assessed for occurrence of Citropsis articulata in each forest. The results indicated a significant (p<0.05) variation in the density of C. articulata with the highest recorded in Kibale National Park. Citropsis articulata generally occurred at moderate altitudinal landscapes (overall elevation = 1200.0 ± 20.73 m) with soils that are moderately acidic (overall pH = 5.7 ± 0.10), low in salinity (overall salinity = 84.0 ± 3.84 mg/l), and moderate levels of macro- and micronutrients. Citropsis articulata was generally associated with plant communities dominated by canopy tree species of genera such as Chryosphyllum, Celtis, Markhamia, Cynometra, Lasiodiscus, Trilepisium, Funtumia, and Diospyros, thus suggesting that C. articulata is a shade-tolerant species. Establishing the ecological requirements of this plant species among other things informs the potential for ex situ production of this plant. This will not only provide alternative sources of plant harvest but also go a long way in relieving the current harvest pressures exerted on the conserved wild populations of this plant species.